Pensamento computacional plugado: uma experiência em creche no município de Bonito/ PA - SILVA, George Lucas Assad da (2024)
Given the current scenario, in which logical reasoning, critical thinking and other problem-solving skills are required, computational thinking emerges as an alternative to assist in teaching and learning. This article describes a playful experience with Computational Thinking at a daycare center in Bonito - PA, with an emphasis on the plugged-in approach through a digital game. It sought to introduce computational thinking from the first years of Early Childhood Education, promoting engaging activities with hardware and software. The implementation of this activity highlights the viability of this initial approach to education. The study enriches the reflection on the relevance of Computational Thinking in children's cognitive development in the first educational stages.